2019
DOI: 10.1016/j.heliyon.2019.e02809
|View full text |Cite
|
Sign up to set email alerts
|

The citizenship values included in intermediate stage Arabic-language textbooks and teachers’ awareness of them in the UAE: A case study

Abstract: This study aimed to identify the extent to which Citizenship values are included in Arabic-language textbooks for the intermediate stage, and teachers' awareness of them in the United Arab Emirates (UAE). In this study, the researchers used a descriptive-analytical approach. Study tools consisted of a list of citizenship values, the presence of which values these textbooks were analyzed for, in addition to a 20-item questionnaire that was administered to 140 teachers. The results showed that a total of 214 ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Meanwhile, in the English dictionary, "Kewarganegaraan" from the origin of the word citizen (citizen) is a person who lives in a nation-state and has certain rights and privileges, as well as obligations to the state, such as loyalty to the government (Althof & Berkowitz, 2006;Azra, 2001). One of the studies related to the value of citizenship in Arabic textbooks by Al Qatawneh reported that the frequency for several citizenship values in textbooks, such as respect for human rights, justice, freedom, courage and interaction with community organizations civil) in four textbooks studied is still lacking (Al-Qatawneh et al, 2019). Sperling (2009) emphasizes the need to create interactions between textbooks and citizenship outcomes to provide learners with lifelong learning skills and increase their sense of responsibility towards society.…”
Section: Concept Of Citizenshipmentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, in the English dictionary, "Kewarganegaraan" from the origin of the word citizen (citizen) is a person who lives in a nation-state and has certain rights and privileges, as well as obligations to the state, such as loyalty to the government (Althof & Berkowitz, 2006;Azra, 2001). One of the studies related to the value of citizenship in Arabic textbooks by Al Qatawneh reported that the frequency for several citizenship values in textbooks, such as respect for human rights, justice, freedom, courage and interaction with community organizations civil) in four textbooks studied is still lacking (Al-Qatawneh et al, 2019). Sperling (2009) emphasizes the need to create interactions between textbooks and citizenship outcomes to provide learners with lifelong learning skills and increase their sense of responsibility towards society.…”
Section: Concept Of Citizenshipmentioning
confidence: 99%
“…This is an important point whose implementation is expected to emerge from the compilers of the book as an extension of information from the regulations that the Government has set, the Byram concept needs to be introduced, and this step is taken to be a reference by the book compilers and to the process of delivering learning in class which the teacher will execute. Al-Qatawneh et al (2019) reported that the lack of content of citizenship values in textbooks is due to the literal lack of experience and compliance by writers and curricula experts in integrating civic values into learning.…”
Section: The Representation Of Citizenship Values In Three Arabic Tex...mentioning
confidence: 99%
See 2 more Smart Citations
“…Prior researches have been conducted on textbooks in the United Arab Emirates (UAE; Abosalem, 2016;Al-Qatawneh et al, 2019;Khine & Yang, 2017). However, most of these studies reported different issues related to school textbooks and not to the textbooks used by higher education institutions.…”
Section: Introductionmentioning
confidence: 99%